1988
DOI: 10.1002/etc.5620070211
|View full text |Cite
|
Sign up to set email alerts
|

Fate of 1,3,6,8-tetrachlorodibenzo-p-dioxin in an outdoor aquatic system

Abstract: Three outdoor pools (5.5 m3) were treated with [14C]1,3,6,8‐tetrachloridibenzo‐p‐dioxin (1,3,6,8‐T4CDD) at concentrations of 98, 245 and 980 ng/L, and the movements and accumulation of the compound were monitored in air, water, sediment and vegetation over a 426‐d period. The concentrations of 1,3,6,8‐T4CDD in the air above the treated pools ranged from 8.4 to 18.8 ng/m3 during the first day after treatment. Total 14C concentration in the water column declined rapidly, with more than 90% lost from the water ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The lesser chlorinated PCDDs/PCDFs generally have higher vapor pressures and lower log K ow values but are more susceptible to biological or chemical degradation than the higher‐chlorinated isomers [24,28]. The results of some studies show that freely dissolved PCDDs/PCDFs have short residency times in the aqueous phase and are rapidly partitioned to suspended particulates and dissolved organic material in the water column [29,30]. Servos et al [30] reported half‐lives in the aqueous phase of 2.6 d for 2,3,7,8‐tetraCDD and 4.0 d for octaCDD in a study using lake enclosures.…”
Section: Resultsmentioning
confidence: 99%
“…The lesser chlorinated PCDDs/PCDFs generally have higher vapor pressures and lower log K ow values but are more susceptible to biological or chemical degradation than the higher‐chlorinated isomers [24,28]. The results of some studies show that freely dissolved PCDDs/PCDFs have short residency times in the aqueous phase and are rapidly partitioned to suspended particulates and dissolved organic material in the water column [29,30]. Servos et al [30] reported half‐lives in the aqueous phase of 2.6 d for 2,3,7,8‐tetraCDD and 4.0 d for octaCDD in a study using lake enclosures.…”
Section: Resultsmentioning
confidence: 99%
“…The half‐life of TCDF in the water column (1.7 to 1.9 d) was similar to those calculated by Servos et al [7] and Corbet etal. [11] for 1,3,6,8‐TCDD (2.6 and 0.6 to 1.2 d, respectively). Both TCDF and 1,3,6,8‐TCDD are hydrophobic, their log K ow s are relatively high (6.5 [29] and 7.1 [30]), and, consequently, they are mainly associated with particles.…”
Section: Discussionmentioning
confidence: 99%
“…Czuczwa and Hites (1986) found that the homologue profiles in the atmosphere and in lake sediments showed a significant enhancement of OCDD relative to all other homologues. In general, PCDF photodegrade much more rapidly than PCDD, and photolytic half-lives increase with increasing level of chlorination for both PCDD and PCDF (Corbet and Webster, 1998;Dobbs and Grant, 1979;Choudhry and Hutzinger, 1982). PCDD/Fs atmospheric degradation in vapor-phase has been suggested to explain the differences between the PCDD/Fs homologue profiles of sources and environmental sinks (Orth et al, 1990;Koester and Hites, 1992).…”
Section: Trends In Homologue Patternmentioning
confidence: 99%
“…PCDD/Fs are highly persistent to chemical transformations and exhibit low biological degradation and high accumulation in biota (Fletcher and Mckay, 1993;Bonn, 1998;Corbet and Webster, 1998). Lake sediments seem to preserve the environmental impact of PCDD/Fs.…”
Section: Introductionmentioning
confidence: 99%